Countercurrent saccharification of lime-pretreated corn stover – Part 1. (January 2017) - Lonkar, Sagar; Liang, Chao; Bond, Austin; Darvekar, Pratik; Brooks, Heather; Derner, John; Yang, Russell; Wilson, Evan; Garcia, Sebastian; Nazmul Karim, M.; Holtzapple, Mark
Abstract: Using the sugar platform, enzymes are a major cost contributor in biofuel production. Conventionally, enzymatic saccharification is performed in batch. To more efficiently use enzymes, a new continuous countercurrent method is explored. Pseudo-continuous countercurrent saccharification was performed on lime-pretreated corn stover at enzyme loadings of 1 mg CTec3/g dry biomass and (1 mg CTec3 + 1 mg HTec3)/g dry biomass and the results were compared with batch. To achieve the same glucan conversion as compared to batch, countercurrent saccharification reduced enzyme loading by 1.6 and 1.4 times at 1 mg protein/g biomass and 2 mg protein/g biomass, respectively. In batch saccharification, the effect of hemicellulase addition was investigated. In countercurrent saccharification, as compared to only 1 mg CTec3/g biomass loading, adding 1 mg HTec3/g biomass increased glucose and xylose yields by 6% and 12%, respectively. The effect of product sugars on enzyme inhibition was studied in batch saccharification. Highlights: In batch saccharification at constant cellulase loading, both glucose and xylose yields increased with hemicellulase addition. In batch saccharification, glucose and xylose yield decreased with increasing initial spiked glucose concentration. In countercurrent saccharification, at enzyme loading of 1 mg CTec3/g biomass, glucose, xylose, and total sugar yields were 61%, 41%, and 55%, respectively. In countercurrent saccharification, at enzyme loading of (1 mg CTec3 + 1 mg HTec3)/g biomass, glucose, xylose, and total sugar yields were 67%, 53%, and 62%, respectively. To achieve the same glucan conversion as compared to batch, countercurrent saccharification reduced enzyme loading by 1.6 and 1.4 times at 1 and 2 mg protein/g biomass, respectively.